Cephalometric analysis of prediction tracings: A comparison of three different methods - Melleiro Gimenez, Carla Maria [UNESP]; Bertoz, André Pinheiro de Magalhães [UNESP]; Cabrini Gabrielli, Marisa Aparecida [UNESP]; Bertoz, Francisco Antônio [UNESP]; Pereira Filho, Valfrido Antonio [UNESP] (Elsevier, 2013)
The purpose of this study was to compare-using cephalometric analysis (McNamara, and Legan and Burstone)-prediction tracings performed using three different methods, that is, manual and using the Dentofacial Planner Plus and Dolphin Image computer programs, with postoperative outcomes. Pre- and postoperative (6 months after surgery) lateral cephalometric radiographs were selected from 25 long-faced patients treated with combined surgery. Prediction tracings were made with each method and compared cephalometrically with the postoperative results. This protocol was repeated once more for method error evaluation. Statistical analysis was made by ANOVA and the Tukey test. The results showed superior predictability when the manual method was applied (50% similarity to postoperative results), followed by Dentofacial Planner Plus (31.2%) and Dolphin Image (18.8%). The experimental condition suggests that the manual method provides greater accuracy, although the predictability of the digital methods proved quite satisfactory. © 2013 World Federation of Orthodontists.
Keywords: Cephalometry; Face; Oral surgery; Orthodontics; Predictability